A crisis in times of crisis: Combating COVID-19 under sanctions in Iran - Sonali Chowdhry; Anna-Katharina Jacobs; Katrin Kamin (Kiel Institute for the World Economy (IfW), 2020)
Iran is one of the countries most affected by COVID-19 worldwide and is considered the epicenter of the outbreak in the Middle East. The growing number of cases in combination with the already ailing economy is putting increasing pressure on the Iranian healthcare system. The delayed reaction of the Iranian government to the outbreak of the pandemic and the low level of political confidence of the population in politics aggravate the crisis situation. In their contribution, the authors show that the far-reaching sanctions Iran has been subject to since the US withdrew from the nuclear agreement make it difficult for the health care system to react quickly to COVID-19. The authors recommend that the European Union, in its role as a responsible "global player", ensure the transfer of medical equipment for humanitarian purposes to Iran and strengthen cooperation efforts in the wake of the pandemic at the level of multilateral institutions. The EU should also play an active role in maintaining the dialogue between the USA and Iran. – – Der Iran gehört weltweit zu den am stärksten von COVID-19 betroffenen Ländern und gilt als Epizentrum für den Ausbruch im Nahen Osten. Die wachsende Fallzahl im Zusammenspiel mit der bereits angeschlagenen Wirtschaft setzt das iranische Gesundheitssystem zunehmend unter Druck. Die verzögerte Reaktion der iranischen Regierung auf den Ausbruch der Pandemie und das geringe Politikvertrauen der Bevölkerung in die Politik verschärfen die Krisensituation. Die Autorinnen zeigen in ihrem Beitrag, dass die weitreichenden Sanktionen, denen der Iran seit dem Ausstieg der USA aus dem Nuklear-Abkommen ausgesetzt ist, eine zügige Reaktion des Gesundheitssystems auf COVID-19 erschweren. Die Autorinnen empfehlen der Europäischen Union in ihrer Rolle als verantwortungsvoller "Global Player", den Transfer von medizinischer Ausrüstung zu humanitären Zwecken in den Iran sicherstellen und die Kooperationsbemühungen im Zuge der Pandemie auf der Ebene multilateraler Institutionen zu stärken. Zudem sollte die EU bei der Aufrechterhaltung des Dialogs zwischen den USA und dem Iran aktiv mitwirken.
Keywords: 330; COVID-19; Iran; Sanctions; Trade Policy; Sanktionen; Handelspolitik